Effects of kilovoltage on image quality and entrance surface dose in lumbar spine digital radiography - Ramli, Hanis Aisyah; Moey, Soo Foon (Iranian Association of Medical Physicists (IAMP), 2019)
Introduction: Digital radiography (DR) possesses a wide dynamic range and has a major advantage in producing an acceptable image of diagnostic value even though overexposure occurs. Lumbar spine (LS) radiography is one of the commonest examinations that give high radiation dose to patients and accounts for the highest collective population dose of any conventional radiographic examination. As such, this study was to ascertain the impact of image quality and entrance surface dose (ESD) with different exposure settings in the antero-posterior (AP) and lateral LS. Materials and Methods: The torso of the PBU-50 phantom was exposed to medium and high kilovoltage (kVp). A total of fourteen images, seven each for AP and lateral LS were obtained. Relative image quality was assessed using Leeds Test Objects TOR (CDR) whilst the entrance surface dose (ESD) was ascertained using the Optically Stimulated Luminescence Dosimeter (OSLD). Results: The Friedman Test indicated a significant difference in image quality when using medium and high kVp; X² (2, N=5) = 23.636, p <0.05. Wilcoxon Signed-Rank Test also reflected a significant difference in ESD between medium and high kVp usage; Z = -2.023, p < 0.05, with higher ESD obtained with medium kVp. Conclusion: Significant differences in image quality and ESD were obtained using medium and high kVp with medium kVp resulting in high contrast but low contrast sensitivity and vice versa. However, lower ESD was obtained with high kVp. The findings of the study indicated that the recommended kVp for AP for LS is from 75kVp to 81kVp whilst for lateral LS, the recommended kVp is from 85kVp to 90kVp for an average adult patient. The usage of the recommended kVp can result in an image of acceptable quality but low ESD consistent with the concept of “as low as reasonably achievable” (ALARA) concept.